2004
DOI: 10.1016/j.cogbrainres.2003.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Handedness, hemispheric asymmetries, and joke comprehension

Abstract: To address the impact of differences in language lateralization on joke comprehension, event-related brain potentials (ERPs) were recorded as 16 left-and 16 right-handed adults read one-line jokes and non-funny control stimuli (''A replacement player hit a home run with my girl/ball,''). In right-handers, jokes elicited a late positivity 500 -900 ms post-stimulus onset that was largest over right hemisphere (RH) centro-parietal electrode sites, and a slow sustained negativity over anterior left lateral sites. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
46
3
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 75 publications
4
46
3
2
Order By: Relevance
“…The early negativity displayed a left anterior scalp distribution, and resembled sustained LAN effects related to processes of working memory (e.g., Vos, Gunter, Kolk, & Mulder, 2001;King & Kutas, 1995;Kluender & Kutas, 1993). Comparable sustained effects have been reported for the comprehension of humorous sentences, and have been linked to extra processing costs of conceptual-semantic reanalysis that enable shifting from one frame into another (Coulson & Lovett, 2004;Coulson & Kutas, 2001). Retrieving new information from long-term memory and reorganizing existing information into a new frame has been proposed to cause increased working memory processes reflected in larger LAN amplitude (Coulson & Kutas, 2001).…”
Section: Discussionmentioning
confidence: 65%
“…The early negativity displayed a left anterior scalp distribution, and resembled sustained LAN effects related to processes of working memory (e.g., Vos, Gunter, Kolk, & Mulder, 2001;King & Kutas, 1995;Kluender & Kutas, 1993). Comparable sustained effects have been reported for the comprehension of humorous sentences, and have been linked to extra processing costs of conceptual-semantic reanalysis that enable shifting from one frame into another (Coulson & Lovett, 2004;Coulson & Kutas, 2001). Retrieving new information from long-term memory and reorganizing existing information into a new frame has been proposed to cause increased working memory processes reflected in larger LAN amplitude (Coulson & Kutas, 2001).…”
Section: Discussionmentioning
confidence: 65%
“…An EEG-study on humor processing revealed that the activation patterns depend on hemispheric asymmetries (Coulson and Lovett 2004) that vary according to gender (Kimura 2000). The counterpart to the higher verbal abilities of women is men's well-established strength in visual-spatial tasks.…”
Section: Discussionmentioning
confidence: 99%
“…The coherence stage of humor often requires a frame-shifting step involving the comparison of data from the stimulus stored in working memory to preexisting, long-term information (17). Thus, making sense of a funny stimulus, particularly in women, may be rooted in the ability of these left-lateralized executive processing regions to store, manipulate, and compare interdependent elements (19), perhaps specializing in positive emotion-eliciting stimuli such as humor (45). Averaged time-series ROI analysis of an isolated section of the DLPFC reveals more robust activation by females only during funny cartoons, further suggesting greater recruitment of executive functioning tools during the development of humor coherence (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The prefrontal cortex (PFC) is likely to correlate with humor integration because it manages response to multiple stimuli while balancing the input of information (18). Specifically, activation of the left lateral inferior frontal gyrus (IFG), encompassing Broca's area, may modulate language comprehension and decoding of stimuli (10), whereas the middle frontal gyrus (MFG), including the dorsolateral PFC (DLPFC), has been implicated in executive functioning that may be crucial to examining, deconstructing, and understanding humorous stimuli (7,(19)(20)(21).…”
mentioning
confidence: 99%